Analyzing and forecasting the gross foreign direct investment towards domestic demand and export in Malaysia economy / Nellyianah Ramidi - Ramidi, Nellyianah (2014)
Foreign Direct Investment (FDI) can be considered as an important economic indicator in developing countries that may influence the other variables changes by bringing in the new technology and improving the workers’ skill. Most of the previous studies using the FDI as a dependent variable but in this study it is used as an independent variable. The main objective of this study is to identify the contribution of gross FDI towards domestic demand, economic growth and export in the Malaysian economy. The annual data from 1970 to 2011 have been used to test the Johansen co- integration test, the Exponential Smoothing approach, the Box-Jenkins approaches and the Granger causality test. The cointegration\ test found that there is at least one co-integration that exists among FDI, EXP, GDP, GFC and HFC at the five percent of significant in the long run. Both of the Exponential Smoothing and the Box-Jenkins approaches are being employed since there are strengths and weaknesses for the applied models. Hence, both of these methods have been used to gain the most accurate prediction by determining the lower forecasting error measures and the information criterion value. After conducted the forecasting test, it is been proven that Box-Jenkins approaches are the most powerful forecasting method compared to exponential smoothing. Whereas, the Granger causality test found new evidence for the actual data which supports the previous study that there is bi- directional causality effect among the variables. However, the causality tests for in- sample and outsample data gained a mixed result for each hypothesis. The outcomes of this study proved that all the developed hypotheses testing for FDI is still valid and considered important as an economic instrument to boost the export, domestic demand and economic growth in Malaysia.